El Excentrico, 1959-06-05 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
June 5, 1959 [5 de junio de 1959]. Ano 9, No. 19. Cover contains a photo of model Rosemary Ramirez in swim attire, leaning against a black oak tree. The headline reads, "Rosemary Ramirez Miss California National Guard."